THE POWER OF CHILD WITNESSES AS EVIDENCE IN CRIMINAL CASE CASES - Gunawan, Wahyu Indra; Makarao, M Taofik; Harahap, Hapendi (Fakultas Hukum, Universitas Islam As-Syafi'iyah, 2023)
Witness testimony is an important factor in all judicial process implementation activities and as evidence that can incriminate or relieve the defendant. Article 1 point 1 of Law Number 13 of 2006 concerning Protection of Witnesses and Victims, states